Navigating the Future of Medicine: How to Find AI-Enhanced Clinical Trials - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2023)
The integration of Artificial Intelligence AI into clinical research marks a pivotal shift in the landscape of medicine. AI-enhanced clinical trials are not ...
Keywords: Drug Discovery; Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation